2021
DOI: 10.7759/cureus.18439
|View full text |Cite
|
Sign up to set email alerts
|

Does Partial Knee Replacement Allow Return to High-Demand Activities?

Abstract: Al-Musawi et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Plancher et al [ 92 ] found that more than 80% of patients achieved an acceptable symptom state in terms of both daily life and sports activities. Regarding the latter, a good satisfaction level was reached in patients under 60 years old, who returned to satisfying and regular physical activities [ 93 ] with good function [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plancher et al [ 92 ] found that more than 80% of patients achieved an acceptable symptom state in terms of both daily life and sports activities. Regarding the latter, a good satisfaction level was reached in patients under 60 years old, who returned to satisfying and regular physical activities [ 93 ] with good function [ 94 ].…”
Section: Discussionmentioning
confidence: 99%